Karakteristik Individu Dan Persepsi Tentang Gaya Pengasuhan Terhadap Hasil Belajar Siswa Kelas X Multi Media I Smk Negeri 2 Sukorejo - Andika Aprilianto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2017)
The study result is influenced by many factors, like internal or external factors. The individual characteristic is one of the internal factors, and perseption of caring style is one of the external factor that can influence the student study result. The study result needs a stimulus from internal individual take the case of talent, interest and attitude, whereas an external stimulus (parent) is a caring style to achieve optimize result. Stimulus that given by parent, is applied through caring style at home. To know as far as the factors can influence student study result, it needs to be known from a research. The research result is expected can give a suggestion that support the increasing of study result. The purposes of the research are to analyze the correlation of individual characters to student study result at x grade of MM1 SMK N 2 Sukorejo. Analyzing the correlation perception of caring style to student study result at x grade of MMI SMK N 2 Sukorejo, analyzing the influence of individual characteristic and perception the caring style to the student study result at x grade of MMI SMK N 2 Sukorejo. The population of this research is the student at x grade of Multi Media I (X MM1) SMK Negeri 2 Sukorejo, there are 37 students. The data analyzing is done by using double analyzing regretion with significant experiment F and significant experiment t. The research’s conclution are (1) The individual characteristic infuelnces positive significant to study result’s increasing, it means that,if be high talent, interest and attitude that is brought by the student to learning process, the study result will be higher. (2) Perception about caring style influence positive significant to study result’s increasing, it means, if it is better the description about interaction between son or daughter and parent as long as carrying out caring activity in educating son or daughter, it will be higher the student study result. (3) The individual characteristic and perception about caring style in a manner of simultaneous having significant influence to student study result, it means the student study result ddepends on student’s talent, interest and attitude along with interaction between student and parent. If be higher talent, interest and attitude along with the interaction between student and parent, it will support the student’s learning process., so, the study result increases too . (4) The large of proportion or variable’s supply of individual characteristic and perception about caring style to the student study result is about 27.6 % whereas the residu of 72.4% is influenced by other factors